INTEGRATION OF NYADRAN VALUES IN SUSTAINABILITY ACCOUNTING BASED ON BARBOUR PERSPECTIVE - Junjunan, Mochammad Ilyas; Jannah, Binti Shofiatul; Buchori, Imam (Journal of Applied Finance and Accounting, 2025)
The Nyadran tradition, a Javanese cultural practice rooted in religious and spiritual values, serves as a metaphorical lens to expand the sustainability accounting paradigm. Using Ian G. Barbour's four perspectives framework—conflict, independence, dialogue, and integration—this study adopts a literature review approach to Nyadran analyse how the Nyadran tradition can enrich sustainability accounting. The findings reveal that Nyadran embodies core values such as ecological harmony, social responsibility, and respect for nature, which resonate deeply with the principles of sustainability. The dialogue and integration perspectives play a pivotal role in bridging the apparent gap between the spiritual essence of Nyadran and the quantitative, data-driven nature of sustainability accounting. Narratives embedded within the Nyadran tradition offer profound insights into sustainability practices, adding depth and meaning to sustainability reporting. In turn, sustainability accounting frameworks can empirically highlight the positive impacts of Nyadran cultural practices on environmental and social well-being. The implications of this research extend beyond traditional paradigms, advocating for the inclusion of moral and spiritual dimensions in sustainability accounting. By integrating Nyadran values, the framework adopts a more holistic approach, emphasising not only environmental and economic aspects but also ethical and spiritual considerations. The study’s novelty lies in its innovative combination of cultural narratives with sustainability accounting, paving the way for a more inclusive and meaningful understanding of sustainability in diverse cultural contexts.